Hypoxic Tumor-Derived Exosomal Long Noncoding RNA UCA1 Promotes Angiogenesis via miR-96-5p/AMOTL2 in Pancreatic Cancer - Zengya Guo; Xiaofeng Wang; Yuhan Yang; Weiwei Chen; Kundong Zhang; Buwei Teng; Chen Huang; Qian Zhao; Zhengjun Qiu (Elsevier, 2020)
The hypoxic microenvironment, an important feature of solid tumors, promotes tumor cells to release exosomes and enhances tumor angiogenesis. However, the detailed functions of hypoxic exosomes and the mechanisms underlying their effects in pancreatic cancer (PC) remain mysterious. Here, we observed that hypoxic exosomes derived from PC cells promoted cell migration and tube formation of human umbilical vein endothelial cells (HUVECs). The long noncoding RNA (lncRNA) UCA1, a key factor, was highly expressed in exosomes derived from hypoxic PC cells and could be transferred to HUVECs through the exosomes. In addition, the expression levels of UCA1 in exosomes derived from PC patients' serum were higher than in healthy controls and were associated with poor survival of PC patients. Moreover, hypoxic exosomal UCA1 could promote angiogenesis and tumor growth both in vitro and in vivo. With respect to the functional mechanism, UCA1 acted as a sponge of microRNA (miR)-96-5p, relieving the repressive effects of miR-96-5p on the expression of its target gene AMOTL2. Collectively, these results indicate that hypoxic exosomal UCA1 could promote angiogenesis and tumor growth through the miR-96-5p/AMOTL2/ERK1/2 axis and therefore, serve as a novel target for PC treatment.